2017
DOI: 10.1002/eap.1568
|View full text |Cite
|
Sign up to set email alerts
|

Floral resource availability from groundcover promotes bee abundance in coffee agroecosystems

Abstract: Patterns of bee abundance and diversity across different spatial scales have received thorough research consideration. However, the impact of short- and long-term temporal resource availability on biodiversity has been less explored. This is highly relevant in tropical agricultural systems for pollinators, as many foraging periods of pollinators extend beyond flowering of any single crop species. In this study, we sought to understand how bee communities in tropical agroecosystems changed between seasons, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
3
19
0
Order By: Relevance
“…The α‐diversity significantly declined with elevation and could be well explained by an interplay of the α‐diversity of floral resources and MAT, which both had a positive effect ( R 2 = 73%). This finding corroborates previous studies on bees and cavity‐nesting hymenopterans, which found close associations of species richness with temperature and the availability of floral resources (Abrahamczyk et al, 2011; Classen et al, 2015; Ebeling et al, 2008; Escobedo‐Kenefic et al, 2020; Fisher et al, 2017; Mayr et al, 2020; Potts et al, 2003). The positive effect of MAT on species richness can be explained by higher metabolic rates of ectothermic organisms under high temperature, fostering net energy intake, and population growth (Brown et al, 2004; Classen et al, 2015; Savage et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…The α‐diversity significantly declined with elevation and could be well explained by an interplay of the α‐diversity of floral resources and MAT, which both had a positive effect ( R 2 = 73%). This finding corroborates previous studies on bees and cavity‐nesting hymenopterans, which found close associations of species richness with temperature and the availability of floral resources (Abrahamczyk et al, 2011; Classen et al, 2015; Ebeling et al, 2008; Escobedo‐Kenefic et al, 2020; Fisher et al, 2017; Mayr et al, 2020; Potts et al, 2003). The positive effect of MAT on species richness can be explained by higher metabolic rates of ectothermic organisms under high temperature, fostering net energy intake, and population growth (Brown et al, 2004; Classen et al, 2015; Savage et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Floral resources at each site (i.e., the total number of flowers) was estimated in sampling plots by using six randomly placed quadrats 1 m x 1 m (covering a proportion of sampling area similar to that reported in Fisher et al, 2017) and summing the number of flowers found within each quadrat.…”
Section: Landscape and Environmental Variablesmentioning
confidence: 99%
“…(https://www.arpalombardia.it/Pages/Aria/qualita-aria.aspx). A map reporting the location of monitoring stations along the investigated landscape is provided in Online resources, FigureS1.An expeditive estimation of floral resources at each site (i.e., the total number of flowers) was performed by using six quadrats 1 m x 1 m (covering a proportion of sampling area similar to that reported inFisher et al, 2017) randomly placed in the flowering green spaces within or closest to the sampling area, and counted the number of flowers found there (as inUshimaru 2014). Flowers were counted considering single or composed inflorescences as units: for Myosotis sp., Galium sp., and Capsella bursa-pastoris, and all Asteraceae the number of inflorescences was counted.…”
mentioning
confidence: 99%
“…The absence of density effects could be due to the low number of pollinators within the study site and its influence on visitation rates (Field et al 2005). The study site was a woodland and the abundance of (Grundel et al 2010, Fisher et al 2017. It should be noted that our design involved only four high-density plots, which may have limited our ability to detect an effect of orchid density on pollinator abundance and behaviour.…”
Section: Foraging Behaviour Of Potential Pollinatorsmentioning
confidence: 99%